ANALISIS PRODUKSI TANAMAN CENGKEH DIDESA TONDO KECAMATAN SIRENJA KABUPATEN DONGGALA - Arinda,M. R. Yantu, Widya (AGROTEKBIS, 2015)
The aims of this study is to analysis the influnce of production factors to production of clove in Tondo Village Sirenja District Donggala Regency. The research was done in Tondo Village at June until August 2014. The population in this research is 215 of clove?s farmer. From that population was taken 15 percent by simple random sampling technique that namely 37 respondents. The analysis used was Cobb-Douglass production function. The result of analysis indicates that the variable of land area (X1), plants (X2), fertilizer (X3), labor (X4), and pesticide (X5)significantly effect simultaneously and partially  to production of clove in Tondo Village, Sirenja District Donggala Regency to ? 20%.